THE INTEGRATED PEATLAND MANAGEMENT SYSTEM (IPMS) - Khalimatus Sa’diyah; Angga Puja Asiandu; Widya Sari (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
Peatland is a rich ecosystem containing many organic components. This ecosystem is composed of plant residue materials that have not undergone a complete decomposition process due to the high water content of the land. Peatland is a rich biodiversity-ecosystem including plants, animals, and microorganisms. The biological resources contained in the peatland are the assets supporting the survival of the community. However, various kinds of damage both caused by humans and caused by nature seriously threaten this ecosystem’s sustainability. This study aimed to formulate the ideas regarding sustainable peatland use as a support for community life. This study is a descriptive qualitative research. While the method used in this study is the literature study, and the data used in this study are secondary data obtained from various sources. Based on the analysis of the collected data, the authors put forward the idea of ​​sustainable peatland use under the name of The Integrated Peatland Management System (IPMS). IPMS is an integrated peatland management system that still pays attention to the conservation aspects by dividing the peatland into three zoning systems. Zone I is an eco-tourism zone, Zone II is a utilization zone, and Zone III is a conservation zone for the peatland ecosystem. The sustainable use of peatlands can be implemented through IPMS to support community life today and in the future. Keywords : Conservation, Eco-tourisms, Peatland, Sustainability, Zoning.